Strength and conditioning in golf: Probability of performance impact - Brearley, S. L.; Coughlan, D.-A.; Wells, J. E. T. (Sport Performance & Science Reports, 2019)
Whether you are a coach, a professional or an amateur golfer, you are sure to have heard the phrase `golf fitness' and have more than likely been advised that you should have a gym routine to help your golf. Given the somewhat vogue status of `golf fitness' at present, there is a large body of information around the topic portraying a complexity which for some creates a barrier to getting started. If you are a professional you are sure to have a busy schedule, and the typical amateur does not have the spare time to devote to over-elaborate routines, so it is important allotted gym-time is used wisely; abolishing components which are unlikely to offer much return. Herein we present a Probability of Performance-Impact Model (Figure 1) which underpins the strength and conditioning (S&C) service provided at the European Tour Performance Institute (ETPI). The aim herein is to add clarity as to how S&C can impact golf performance, and reassure that gym programmes need not be complicated. The authors hope this will encourage players of all levels to make that behaviour change towards a healthier lifestyle and compliment their golf training with a no-frills gym routine.